2019
DOI: 10.7150/jca.28680
|View full text |Cite
|
Sign up to set email alerts
|

The role of postoperative radiotherapy for completely resected pIIIA-N2 non-small cell lung cancer patients with different clinicopathological features: a systemic review and meta-analysis

Abstract: Background : The role of postoperative radiotherapy (PORT) in completely resected pathological stage IIIA-N2 (pIIIA-N2) non-small cell lung cancer (NSCLC) remains controversial. This meta-analysis aimed to assess the effect of PORT in patients with pIIIA-N2 NSCLC on the basis of clinicopathological features. Methods : The PubMed, PubMed Central (PMC), Embase, Web of Science, and Cochrane Library were searched for relevant studies. The main outcomes were overall survival (OS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Our findings suggested that among patients with lower prognostic scores, there was no statistical difference in cancer‐specific survival between the PORT group and the non‐RT group, whereas patients with higher prognostic scores treated with PORT demonstrated a significantly statistical difference in the survival, compared with those in whom PORT was not used. Therefore, taken together with previous findings, 15‐18 these results indicated that treatments for IIIA/N2 NSCLC should be individualized. Further studies on the basis of patient prognostic‐score to determine which patients with resected IIIA/N2 NSCLC may be able to benefit most from PORT are required.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our findings suggested that among patients with lower prognostic scores, there was no statistical difference in cancer‐specific survival between the PORT group and the non‐RT group, whereas patients with higher prognostic scores treated with PORT demonstrated a significantly statistical difference in the survival, compared with those in whom PORT was not used. Therefore, taken together with previous findings, 15‐18 these results indicated that treatments for IIIA/N2 NSCLC should be individualized. Further studies on the basis of patient prognostic‐score to determine which patients with resected IIIA/N2 NSCLC may be able to benefit most from PORT are required.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, patients with stage IIIA/N2 NSCLC are a heterogeneous population with different clinicopathological characteristics. Some clinicopathological factors have been reported to be independent risk factors for patients with poor prognosis, such as age, sex, grade, T stage, chemotherapy and LNR 14–18 . Mao et al 32 analyzing data from 1809 patients, developed a nomogram to predict the survival of stage IIIA–N2 NSCLC after surgery, based on certain clinical factors, such as age, sex, grade, histology, positive lymph nodes and lymph nodes examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 In general, in patients with different clinicopathological features, only selected patients benefit from PORT. 21 Several clinicopathological factors such as number of N2 status, smoking history, tumor size and sex have been reported to be associated with patient survival rates. 7 , 8 , 9 , 10 , 11 , 12 Therefore, the estimate of the benefit of PORT for pIIIA-N2 NSCLC should be individualized.…”
Section: Discussionmentioning
confidence: 99%
“…The role of postoperative radiation (PORT) in resectable non-small cell lung cancer (NSCLC) remains controversial, particularly in stage III disease [1] , [2] . The ANITA trial that indicated that patients with pN2 disease could benefit from PORT but patients with pN1 disease did not [3] .…”
Section: Introductionmentioning
confidence: 99%